Neuronal FcεRIα directly mediates ocular itch via IgE-immune complex in a mouse model of allergic conjunctivitis - Huan Cui; Fan Liu; Yehong Fang; Tao Wang; Bo Yuan; Chao Ma (Journal of Neuroinflammation, 2022)
Abstract Background Classical understanding of allergic conjunctivitis (ACJ) suggests that ocular itch results from a mast cell-dependent inflammatory process. However, treatments that target inflammatory mediators or immune cells are often unsatisfying in relieving the stubborn itch symptom. This suggests that additional mechanisms are responsible for ocular itch in ACJ. In this study, we aim to determine the role of neuronal FcεRIa in allergic ocular itch. Methods Calcium imaging was applied to observe the effect of IgE-immune complex in trigeminal neurons. Genomic FcεRIa knockout mice and adeno-associated virus (AAV) mediated sensory neuron FcεRIa knockdown mice were used in conjunction with behavioral tests to determine ocular itch. In addition, immunohistochemistry, Western blot and quantitative RT-PCR were used for in vitro experiments. Results We found that FcεRIα was expressed in a subpopulation of conjunctiva sensory neurons. IgE-IC directly activated trigeminal neurons and evoked acute ocular itch without detectible conjunctival inflammation. These effects were attenuated in both a global FcεRIa-knockout mice and after sensory neuronal-specific FcεRIa-knockdown in the mouse trigeminal ganglion. In an ovalbumin (OVA) induced murine ACJ model, FcεRIα was found upregulated in conjunctiva-innervating CGRP+ sensory neurons. Sensory neuronal-specific knockdown of FcεRIa significantly alleviated ocular itch in the ACJ mice without affecting the immune cell infiltration and mast cell activation in conjunctiva. Although FcεRIα mRNA expression was not increased by IgE in dissociated trigeminal ganglion neurons, FcεRIα protein level was enhanced by IgE in a cycloheximide-resistance manner, with concordant enhancement of neuronal responses to IgE-IC. In addition, incremental sensitization gradually enhanced the expression of FcεRIα in small-sized trigeminal neurons and aggravated OVA induced ocular itch. Conclusions Our study demonstrates that FcεRIα in pruriceptive neurons directly mediates IgE-IC evoked itch and plays an important role in ocular itch in a mouse model of ACJ. These findings reveal another axis of neuroimmune interaction in allergic itch condition independent to the classical IgE-mast cell pathway, and might suggest novel therapeutic strategies for the treatment of pruritus in ACJ and other immune-related disorders.